Investigation of barium iron oxides for CO2 capture and chemical looping oxygen uncoupling - Saqline, Syed (2024)
The performance of two underexploited ternary oxides – Ba3Fe2O6 and Ba5Fe2O8 are investigated for carbon dioxide capture and chemical looping oxygen uncoupling. The ternary compound Ba3Fe2O6 was found to have a structure characterised by space group Pa3¯. Experimental results have shown that both Ba3Fe2O6 and Ba5Fe2O8 are capable of cyclically capturing CO2 at temperatures above 800 °C. Ba5Fe2O8 demonstrated superior CO2 capture performance compared to Ba3Fe2O6, with consistent gravimetric CO2 uptake capacities of 4.35 wt% and 13.39 wt% at 900 °C and 1000 °C, respectively, over 20 cycles. In comparison, Ba3Fe2O6 demonstrated high initial CO2 uptake capacities which deteriorated cyclically, with 20 cycle average capacities of 7.73 wt% and 11.99 wt% at 900 °C and 1000 °C, respectively. Ba3Fe2O6 also exhibits excellent recyclability and satisfactory chemical looping oxygen uncoupling (CLOU) activity over temperature swing cycles between 550 °C and 950 °C. In contrast, the strong affinity with CO2 makes Ba5Fe2O8 unsuitable for application in chemical looping oxygen uncoupling or chemical looping air separation, especially in the presence of substantial partial pressures of CO2.